Effect of Decellularization Protocol on the Mechanical Behavior of Porcine Descending Aorta - John C. Fitzpatrick; Peter M. Clark; Franco M. Capaldi (International Journal of Biomaterials)
Enzymatic-detergent decellularization treatments may use a combination of chemical reagents to reduce vascular tissue to sterilized scaffolds, which may be seeded with endothelial cells and implanted with a low risk of rejection. However, these chemicals may alter the mechanical properties of the native tissue and contribute to graft compliance mismatch. Uniaxial tensile data obtained from native and decellularized longitudinal aortic tissue samples was analyzed in terms of engineering stress and fit to a modified form of the Yeoh rubber model. One decellularization protocol used SDS, while the other two used TritonX-100, RNase-A, and DNase-I in combination with EDTA or sodium-deoxycholate. Statistical significance of Yeoh model parameters was determined by paired t-test analysis. The TritonX-100/EDTA and 0.075% SDS treatments resulted in relatively variable mechanical changes and did not effectively lyse VSMCs in aortic tissue. The TritonX-100/sodium-deoxycholate treatment effectively lysed VSMCs and was characterized by less variability in mechanical behavior. The data suggests a TritonX-100/sodium-deoxycholate treatment is a more effective option than TritonX-100/EDTA and SDS treatments for the preparation of aortic xenografts and allografts because it effectively lyses VSMCs and is the least likely treatment, among those considered, to promote a decrease in mechanical compliance.